Sexuality and Psychological Well-being in Breast Cancer Survivors: Insights from the Biopsychosocial Perspective - Tania Angelita Iora Guesser; Victor Hugo Guesser Pinheiro; Cristine Lima Alberton; Stephanie Santana Pinto (Revista Brasileira de Cancerologia)
Introduction: Breast cancer survivors face psychological, social, and cultural challenges, often related to anxiety, depression, and sexuality issues. These experiences are influenced by physical and emotional changes resulting from oncological treatment, as well as sociocultural taboos. Objective: To highlight the importance of the biopsychosocial model in managing the psychological and social impacts on women who have survived breast cancer and participated in the WaterMama study, emphasizing the essential role of health education groups in promoting the emotional and sexual well-being of these patients and providing practical insights for healthcare professionals seeking to adopt a more integrative and humanized approach. Method: Descriptive study with a qualitative approach, based on the biopsychosocial model. The investigation focused on analyzing the interactions and mutual support established among these women in health education groups, with an emphasis on the psychological and social dynamics experienced by the participants. Results: Group interactions and peer support emerged as key factors in reducing psychological and social impacts, promoting greater social connection, resilience, and quality of life. The adoption of the biopsychosocial model enabled a comprehensive approach to the needs of these women, highlighting the relevance of sexuality as an integral part of mental health and well-being. Conclusion: Integrative strategies, such as support and health education groups, are essential components in the care of this population, with significant benefits for their physical, psychological, and social health.